Corporate Governance and Integrated Reporting and its Impact on Banking’s Firm Value (Evidence from Indonesia) - Oktawijaya, Andre; Carolina, Yenni (University of Merdeka Malang, 2023)
This study aims to analyze the effect of corporate governance on integrated reporting and its impact on firm value as measured by leverage, return on assets, liquidity, and firm size as control variables. The analysis technique in this study uses multiple linear regression using secondary data, assisted by E-Views software. The population used is banking companies listed on the Indonesia Stock Exchange for the period of 2017-2020. The sample selected was eight banking companies with purposive sampling, namely with the following criteria: listed on the IDX with a minimum listing year of 2017 and issuing financial statements and ACGS for the period of 2017-2020. The results of this study conclude that corporate governance and integrated reporting affect firm value, but corporate governance does not affect integrated reporting